Procedings of the British Machine Vision Conference 2005 2005
DOI: 10.5244/c.19.21
|View full text |Cite
|
Sign up to set email alerts
|

Double Contour Active Shape Models

Abstract: Statistical shape models are often learned from examples based on landmark correspondences between annotated examples. A method is proposed for learning such models from contours with inconsistent bifurcations and loops. It is evaluated on the task of segmenting tibial contours in knee radiographs. Results are presented using various features, distance weighted K−nearest neighbours and differing eigenspace shape constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…To the best of our knowledge, only the studies by Anthony et al [1] and Shamir et al [22] focused on knee joint area localization. While the problem of knee joint area localization can be implicitly solved by annotating the anatomical bone landmarks using deformable models [21,15], it would be unfeasible to perform large-scale studies since the use of these algorithms is computationally costly. Currently, despite the presence of multiple approaches, no studies have reported so far their applicability among different datasets.…”
Section: Related Workmentioning
confidence: 99%
“…To the best of our knowledge, only the studies by Anthony et al [1] and Shamir et al [22] focused on knee joint area localization. While the problem of knee joint area localization can be implicitly solved by annotating the anatomical bone landmarks using deformable models [21,15], it would be unfeasible to perform large-scale studies since the use of these algorithms is computationally costly. Currently, despite the presence of multiple approaches, no studies have reported so far their applicability among different datasets.…”
Section: Related Workmentioning
confidence: 99%
“…The method was evaluated on a data set of 30 standard clinical x-rays (see also [10]). Images of left knees were mirrored so that they appeared as right knees.…”
Section: Methodsmentioning
confidence: 99%
“…In medical applications, especially, it is desirable to have an indication of the certainty of a measurement and to cope with structures that overlap or are in close proximity. The proposed method is evaluated for the segmentation of the knee joint for the purpose of the measurement of joint space which is an important biomarker for the assessment of osteoarthritis [10]. …”
Section: Introductionmentioning
confidence: 99%